Genome-Wide Analysis of the PIN Auxin Efflux Carrier Gene Family in Coffee - Huang, Xing (Plants (Basel), 2020)
Coffee is one of the most popular beverages around the world, which is mainly produced from the allopolyploid Coffea arabica. The genomes of C. arabica and its two ancestors C. canephora and C. eugenioides have been released due to the development of next generation sequencing. However, few studies on C. arabica are related to the PIN-FORMED (PIN) auxin efflux transporter despite its importance in auxin-mediated plant growth and development. In the present study, we conducted a genome-wide analysis of the PIN gene family in the three coffee species. Totals of 17, 9 and 10 of the PIN members were characterized in C. Arabica, C. canephora and C. eugenioides, respectively. Phylogenetic analysis revealed gene loss of PIN1 and PIN2 homologs in C. arabica, as well as gene duplication of PIN5 homologs during the fractionation process after tetraploidy. Furthermore, we conducted expression analysis of PIN genes in C. arabica by in silico and qRT-PCR. The results revealed the existence of gene expression dominance in allopolyploid coffee and illustrated several PIN candidates in regulating auxin transport and homeostasis under leaf rust fungus inoculation and the tissue-specific expression pattern of C. arabica. Together, this study provides the basis and guideline for future functional characterization of the PIN gene family.